Ciptakan Generasi Emas Bebas Anemia Melalui Edukasi Gizi Remaja - Irma Irma; Novia Nurul Chaerunnisa; Yade Kurnia Yasin; Andi Muhammad Zulkifli; Irfan Yunus (PT. Mediatama Zayna Indonesia, 2026)
Anemia in adolescent girls, caused by menstruation and nutritional deficiencies, particularly iron deficiency, is a significant problem at Madrasah Putri Al Bashirah, where 62% of female students have low hemoglobin levels. This figure is considerably higher than the national prevalence of anemia in adolescent girls (18% according to the 2023 Indonesian Health Survey/SKI). Therefore, this program aimed to increase the knowledge and awareness of 29 female students regarding the importance of anemia prevention. An educational intervention using an educational fan (Kipas Edukasi) media with a pre-post test design was conducted to encourage compliance with the Iron tablet (TTD) consumption in order to foster a healthy golden generation. Statistical analysis using a paired t-test revealed a significant effect (p<0.001) after the intervention, marked by an increase in knowledge between the pre-test and post-test results. Furthermore, the intervention positively impacted the students’ perspectives on TTD consumption compliance, based on the acknowledgment and willingness of all 29 adolescent girls. In conclusion, the educational intervention using the educational fan media was effective in enhancing knowledge and changing perspectives among adolescent girls regarding regular iron tablet consumption to reduce the incidence of anemia.